Critical success factors for UiTM contractors in Malaysia / Hamimah Adnan … [et al.] - Adnan, Hamimah; Yusof, Faridah; Mohd Yusuwan, Norazian; Bachik, Fauziah (Research Management Institute (RMI), 2012)
Chua et al. (1999) stated that the factors which bring to the success of a construction project were caused by four main aspects only, which are the projects characteristics, contractual arrangements, projects participants and interactive process. On the other hand, every factor that affects the success of the construction projects can only be analyzed in general without taking the allocated project objectives into account (Sanvido et al. (1999). In reality, these factors have different roles for different project objectives (Jaselskis and Ashley, 1991). In addition, James et al. (1996) stressed that generally, an excellent quality of a project can only be improved when interaction process involved in the project. On the other hand, the constructability factor in a project has been identified as a factor which can save time and cost as well as increase the construction project quality (Construction Management Committee of ASCE Construction Division, 1991). Jaselskis and Ashley (1991) stressed on the optimum use of the construction sources as the major factor to lead the success of the construction projects. Hence, clearly there are many critical factors being identified as the factor that leads to the construction project success. However, differences of factors are more critical toward different project objectives. There are no complete list of answers on what are the critical factors which lead to a success of construction project based on the objective of the project schedule, budget and performance. Therefore, this research is conducted to determine the critical success factors on time, quality and cost on UiTM contractors works.